Perilaku Bullying pada Siswa Mts Al-Washliyah Kecamatan Tanjung Beringin Kabupaten Serdang Bedagai - Juniawati Sihombing; Hasyimsyah Nasution; Hotmatua Paralihan Harahap (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Bullying behavior in the school environment is a social problem that has a serious impact on the psychological and social development of students. This study aims to describe the forms of bullying among students at MTs Al-Washliyah in Tanjung Beringin District, Serdang Bedagai Regency, analyze the causal factors, and review them from an Islamic perspective and strategies for handling them. The study used a qualitative approach with field research. Data were collected through observation, semi-structured interviews with the principal, teachers, and students, and documentation, then analyzed descriptively and analytically. The results showed the presence of verbal, physical, and relational bullying, with verbal bullying being the most dominant form. Causal factors include students' internal conditions, family parenting patterns, the influence of the social environment and social media, and weak moral development. From an Islamic perspective, bullying is seen as a reprehensible act because it contradicts noble moral values. Efforts to address this are carried out through prevention, direct intervention, and moral development based on Islamic teachings.